Multiphase Model for the Prediction of Shrinkage Cavity, Inclusion and Macrosegregation in a 36-Ton Steel Ingot - Xie, Mengye; Shen, Houfa (Frontiers in Materials, 2020)
A five-phase model consisting of liquid phase, columnar dendrites, equiaxed grains, air and inclusion (discrete phase) is developed to predict the shrinkage cavity, inclusion distribution and macrosegregation simultaneously during solidification of a 36-ton steel ingot. The air phase is introduced to feed the shrinkage cavity and no mass or species exchange with other phases occurs. The transport and entrapment of inclusions are simulated using a Lagrangian approach. The predicted results agree well with the experimental results. The characteristics of inclusion distribution is figured out. A thin layer of inclusions tends to form close to the mold wall, and more inclusions reside in the last solidified segregation channels. Inclusion is easy to aggregate near the riser neck, and it is dragged by the solidification shrinkage. The influence of inclusion on macrosegregation is comparatively small, while the solidification shrinkage affects the formation of macrosegregation significantly and makes the simulation result more accurate.